Analysis of Mathematical and Graphical Relationships Between Volume, Speed, and Density of Traffic with Greenshields and Underwood Models (Case Study: Ir. H. Juanda Street, Central Jakarta) - Ignasius Nugroho, Reinhart; Hagni Puspito, Imam (Rekayasa Sipil, 2025)
DKI Jakarta Province is one of the centers of transportation progress in Indonesia. One of the locations around Jakarta that is of great concern is the Juanda area, specifically on Ir. H. Juanda Street, Central Jakarta. The daily activity of motorized vehicle users on this road looks very congested on busy days such as Wednesday and Friday and quieter on Sunday. All vehicle activities on the road can be modeled to determine the relationship based on the traffic flow characteristics. The data obtained in the field, such as volume and speed, will be processed first with basic relationships using PKJI standard, then can be analyzed with mathematical and graphical relationships to present the relationship between volume, speed, and density of traffic on Wednesday, Friday, and Sunday on Ir. H. Juanda Street, Central Jakarta with Greenshields and Underwood models. The analysis results according to the relationship between volume, speed, and density of traffic with PKJI standard is suitable for Ir. H. Juanda Street on the Underwood model because it shows the strongest relationship with the r value of 0,940475 between speed and density to produce the equation Us = 46,22 exp (-0,02 D), Q = 55,84 Us ln (46,22/Us), and Q = 46,22 D exp (-0,02 D). The Underwood model has the best accuracy on Sunday, with the r2 value of 0,885001. The determination coefficient shows how well the regression prediction of the model is based on field data with an accuracy of 88,5%. The highest maximum volume was obtained using the Underwood model on Wednesday at 1.319,07296 SMP/hour.